The golden lancehead Bothrops insularis (Serpentes: Viperidae) relies on two seasonally plentiful bird species visiting its island habitat - Marques, Otavio A. V.; Martins, Marcio; Develey, Pedro F.; Macarrao, Arthur [UNESP]; Sazima, Ivan (Taylor & Francis Ltd, 2012)
Adult individuals of the island pitviper Bothrops insularis have a diet based on birds. We analysed bird species recorded in the gut of this snake and found that it relies on two out of 41 bird species recorded on the island. When present, these two prey species were among the most abundant passerine birds on the island. A few other migrant birds were very occasionally recorded as prey. A resident bird species (Troglodytes musculus) is the most abundant passerine on the island, but seems able to avoid predation by the viper. Bothrops insularis is most commonly found on the ground. However, during the abundance peak of the tyrannid passerine Elaenia chilensis on the island, more snakes were found on vegetation than on the ground. We suggest that one cause may be that these birds forage mostly on vegetation, and thus cause the snakes to search for prey on this arboreal substratum.
Keywords: endemic snake; Bothrops insularis; Queimada Grande Island; Diet; migrant birds; abundant birds